Hysterectomies: An Audit at A Tertiary Care Public Sector Hospital in Lahore, Pakistan - Madiha Iqbal, Asmaa Qureshi, Shahzad Saeed, Rabia Basharat, Farah Kalsoom, Farrukh Kamal, Rubina Farrukh, Khawaja Moeen Ud Din, Muhammad Ali Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Hysterectomy is a common gynecological surgery worldwide. Thorough preoperative clinical and radiological assessment of the patients followed by histopathological evaluation of the specimens is mandatory for providing good health care services to the patients. Objective: The objective of the study was to analyze the spectrum of histopathological findings in hysterectomy specimens & correlate them with their clinical & radiological findings. Patients and Methods: This was a retrospective, descriptive, cross sectional study, carried out at the Pathology Department of Fatima Jinnah Medical University, Lahore. All the gynecological hysterectomies received at the department from 1st December 2018 to 30th November 2020 were included in the study. Data collected, included age of the patient, clinical presentation, radiological findings, type of hysterectomy performed and complete histopathology report of the specimen. Data was analyzed using SPSS version 17. Results: A total of 637 hysterectomy specimens were included in the study. The age of the patients ranged from 22 years to 80 years with a mean age of 46 ± 9 years. The commonest clinical indication was a uterine mass (47.7%). Most frequent preoperative radiological (USG/ CT scan/MRI) finding was uterine mass/polyps (52%). The commonest surgical procedure was total abdominal hysterectomy (52.4%). On histopathological evaluation, 99% of the cases showed chronic cervicitis. The commonest diagnosis in the uterine corpus was leiomyoma. Uterine malignancy accounted for 7.3% of the cases and 4.7% of hysterectomies were done for ovarian malignancies. Practical implicationThis study aims to highlight the need for a multi-disciplinary audit for all hysterectomy cases to reduce the incidence of this surgery & for better patient care & management. Conclusion: Hysterectomy is a major, invasive surgical procedure. A vigilant preoperative clinical and radiological evaluation of the patient can reduce the incidence of this surgery. Histopathological analysis of all hysterectomy specimens is mandatory for diagnosis of benign and malignant conditions, recognition of precancerous lesions and detection of incidental findings. Keywords: Hysterectomies, Audit, Leiomyoma, preoperative radiological evaluation, histopathological evaluation